2021
DOI: 10.3390/toxins13020074
|View full text |Cite
|
Sign up to set email alerts
|

Toxin–Antitoxin Systems in Pathogenic Bacteria

Abstract: Toxin–antitoxin (TA) systems, which are ubiquitously present in plasmids, bacterial and archaeal genomes, are classified as types I to VI, according to the nature of the antitoxin and to the mode of toxin inhibition [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Because of their association with virulence in bacterial pathogens, TA systems have been recognized as promising therapeutic targets. , We found that the antitoxin HigA can repress the exsA and amrZ promoters to reduce the expression of T3SS and T6SS, respectively, both of which are responsible for virulence of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because of their association with virulence in bacterial pathogens, TA systems have been recognized as promising therapeutic targets. , We found that the antitoxin HigA can repress the exsA and amrZ promoters to reduce the expression of T3SS and T6SS, respectively, both of which are responsible for virulence of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 97%
“…Antitoxins are typically susceptible to cellular protease degradation under various stresses; this increases the toxin/antitoxin ratio and causes growth inhibition. Emerging evidence has shown that the type II TA systems are involved in pathogen adaptation to host tissues and chronic or recurrent infections. For instance, Agarwal et al reported that the VapBC type II TA systems from Mycobacterium tuberculosis is a key pathogenesis regulator; the authors demonstrated that the toxin VapB inhibits the expression of virulence-associated proteins and that the cellular VapB/VapC ratio is crucial for M. tuberculosis to adapt to host environments .…”
mentioning
confidence: 99%
“…These have been implicated to help bacteria adapt to different stress conditions by downregulating metabolism and potentiating transition into dormant like stage ( Unterholzner et al, 2013 ; Chan et al, 2016 ). In addition to slowing down of bacterial metabolism, TA systems are also shown to be essential for persistence and bacterial pathogenesis ( Wen et al, 2014 ; Yang and Walsh, 2017 ; Alonso, 2021 ). The large number of TA systems in the genome of M. tuberculosis makes it difficult to perceive the involvement of individual TA systems in the pathogen biology.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of plasmid maintenance include the production of toxin-antitoxin (TA) systems. Toxin-antitoxin systems are important for plasmid maintenance; toxins produced by plasmids kill cells that have lost plasmids during cell division, thus selecting for plasmid-carrying cells ( 17 ). Plasmid pSBP2_mcr4 encodes three different type II TA systems of the RelE/ParE type, Phd/YefM family, and HiCAB type.…”
Section: Observationmentioning
confidence: 99%